Clitics between syntax and lexicon - Gerlach, Birgit (Amsterdam ; Philadelphia : J. Benjamins, 2002)
As a typical interface phenomenon, clitics have become increasingly important in linguistic theory during the last decade. The present book contributes to the recent discussion and first provides a comprehensive overview of clitic sequencing, clitic placement and clitic doubling in the major Romance languages. In addition, new data from a northern Italian dialect are introduced. The author then gives a critical summary of the current morphological analyses of clitic phenomena. She also discusses recent Optimality-theoretical analyses of clitic combinations and clitic placement and shows how th.
Clitics between Syntax and Lexicon; Editorial page; Title page; LCC data; Contents; Acknowledgements; Abbreviations; Chapter 1: Introduction; Chapter 2: The status of Romance clitics between words and affixes; Chapter 3: Clitics in the lexicon; Chapter 4: Clitic sequences; Chapter 5: Syntax at the interfaces: Clitic placement and clitic doubling; Chapter 6: Summary; References; Appendix; Language index; Name index; Subject index; Linguistik Aktuell/Linguistics Today.
Includes bibliographical references (pages 241-253) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Grammar, Comparative and general -- Clitics; Romance languages -- Clitics; Clitiques; Langues romanes -- Clitiques; LANGUAGE ARTS & DISCIPLINES; Linguistics / General; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax; Grammar, Comparative and general -- Clitics; Romance languages -- Clitics; Clitische elementen; Voornaamwoorden; Romaanse talen; Languages & Literatures; Philology & Linguistics; Gramática comparada (aspectos fonológicos); Sintaxe; Morfologia (lingüística); Línguas indo-européias ocidentais